War and peace in the borderlands of Myanmar the Kachin ceasefire, 1994-2011 - Sadan, Mandy (NIAS studies in Asian topics, 2016)
This book brings together local activists with international academics and acclaimed independent researchers to reflect on these experiences from different perspectives. They also raise important and enduring questions about the social, economic and political development of Myanmar's 'border regions'